Copper-Catalyzed Si–B Bond Activation in the Nucleophilic Substitution of Primary Aliphatic Triflates - Scharfbier, Jonas; Oestreich, Martin (Synlett, 2016)
A method for the nucleophilic displacement of the triflate leaving group attached to terminally functionalized alkyl groups with nucleophilic silicon is reported. Copper catalysis is used to release the silicon nucleophile from Suginome’s Si–B reagent. The functional group tolerance is excellent, and halide leaving groups do also work with the same protocol.
Keywords: chemoselectivity; copper; nucleophilic substitution; silicon; transmetalation